A Morphometric Analysis of Karangan Watershed East Kutai Regency, Using Remote Sensing Data and GIS Techniques: Morphometric Analysis of Karangan Watershed East Kutai Regency, Using Remote Sensing Data and GIS Techniques - Suryanto, Joko; Amprin, Amrpin; Krisbiyantoro, Joko; Anisum, Anisum (Jurnal Agritechno, 2024)
Watershed management requires information on the characteristics of the watershed, particularly its morphometric parameters. The Geographic Information System (GIS) techniques and remote sensing products such as the Digital Elevation Model (DEM) can used in analyzing watershed morphometric parameters. This research aims to determine the Karangan watershed’s morphometric parameter divided into linear, areal, and relief aspects. The study uses Shuttle Radar Topography Mission (SRTM) DEM data and GIS techniques to obtain morphometric parameters. The drainage network analysis obtained from SRTM DEM data extraction shows that the Karangan watershed has seven river orders with very low drainage density and fine drainage texture. The parameters of drainage density, drainage texture, infiltration number, and constant channel maintenance indicate that the watershed has low surface runoff, making it less susceptible to erosion. The parameters of low bifurcation ratio and high elongation ratio suggest that the shape’s watershed is circular, with the characteristic rainfall quickly concentrated into stream flow. The hypsometric integral value revealed that the Karangan watershed is in the mature geomorphological development phase and dominated by fluvial landforms.